Cookies from Wheat Flour and Banana Flour with the Addition of Moringa Leaf Flour (Moringa oleifera) - Nabela Eka Yulia; Laili Susanti; Lukman Hidayat; Ulfah Anis (Badan Penerbitan Fakultas Pertanian (BPFP), 2022)
The dependence on the use of wheat flour in the manufacture of bakery products should be reduced to reduce wheat imports. One alternative that can be done is substituting wheat flour with other flour, for example, banana flour. In their manufacture, cookies substituted for banana flour produce a brown color that is not preferred. Therefore, to fix this, in making cookies, the addition of green moringa leaf flour is carried out. Besides being expected to improve the cookies' color, Moringa leaf flour also contains good nutrients. Moringa leaf flour contains protein, minerals, vitamins, essential amino acids, and antioxidants. The nutrients contained in moringa leaf flour have the potential to be nutritious food additives and beneficial to health. The purpose of this study was to determine the effect of the addition of moringa leaf flour on wheat flour cookies and banana flour on physical characteristics (moisture content, color, and texture), chemical characteristics (protein content and ash content), and organoleptic (color, aroma, taste, texture, and overalls). This study used a complete randomized design (CRD) with 1 factor: the percentage of addition of Moringa leaf flour, 0%, 2.5%, 5%, 7.5%, and 10%. Adding Moringa leaves to manufacture cookies from wheat flour and banana flour significantly affects the moisture content, texture, color, protein content, and ash content of the cookies produced. The most preferred cookies are cookies with the addition of 5% moringa leaf flour.